The role of social media in shaping the animal protection movement in indonesia - Aji, Angga Prawadika (Faculty of Communications Science, Dr. Soetomo University, 2019)
In the past decade, the number of community-based animal protection movements has shown a significant increase in Indonesia. These groups are actively fighting for animal rights, protection, and conservation while continuing to expand the influence and attract new members through various channels, especially social media. This article seeks to see the contribution of the social media strategy used by animal rights groups to the three basic elements of a social movement: collective identity, actual mobilisation, and network organisation. How social media, especially Face book and Instagram, are used by animal rights groups to achieve their ultimate goal as a social movement. This analysis also seeks to map the character of the movement for animal protection in Indonesia in the realm of new media based on their ideology, strategies, and objectives they want to achieve.